الآراء الجمالية وأهميتها في تجويد فن الخط العربي: دراسة تحليلية: دعاء بنت محمد داود الأشعري - دعاء بنت محمد داود الأشعري (Journal of Calligraphy, 2021)
The art of calligraphy is considered one of the Islamic visual and sacred arts, and that the Islamic nation dealt with authorship and intonation in Arabic calligraphy and improving the engineering structure in terms of beautifying it because it is an art related to the Islamic faith, so this study aims to shed light on the most important aesthetic views that were mentioned regarding the art of Arabic calligraphy within A systematic perspective that includes the aesthetic context and rooted the principle of beauty in this art. The method used in this study is the descriptive analytical method, which describes and analyzes the opinions and aesthetic characteristics inherent within the art of Arabic calligraphy. The study concluded that the sum of these aesthetic opinions mentioned regarding the art of Arabic calligraphy had a great impact in imparting values and aesthetic dimensions to the art of Arabic calligraphy on the one hand, and on the other hand, they had a prominent role in its development, refinement and perfection.